2013
DOI: 10.1002/eji.201343579
|View full text |Cite
|
Sign up to set email alerts
|

CD27 costimulation contributes substantially to the expansion of functional memory CD8+T cells after peptide immunization

Abstract: Naive T cells require signals from multiple costimulatory receptors to acquire full effector function and differentiate to long-lived memory cells. The costimulatory receptor, CD27, is essential for optimal T-cell priming and memory differentiation in a variety of settings, although whether CD27 is similarly required during memory CD8 + T-cell reactivation remains controversial. We have used OVA and anti-CD40 to establish a memory CD8 + T-cell population and report here that their secondary expansion, driven b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…CD27 stimulation significantly increases the magnitude of T cell responses to peptide or protein antigen in murine models [3••;17;60•] and synergizes with IFN-1 in both the expansion of effector CD8 + T cells and the subsequent development of CD8 + T cell memory. As the variegated influences of CD27 on effector and memory T cell development become more understood, there may be opportunities select regimens to support central, effector or tissue resident memory cells.…”
Section: Therapeutic Implementation Of Targeting Cd27mentioning
confidence: 99%
“…CD27 stimulation significantly increases the magnitude of T cell responses to peptide or protein antigen in murine models [3••;17;60•] and synergizes with IFN-1 in both the expansion of effector CD8 + T cells and the subsequent development of CD8 + T cell memory. As the variegated influences of CD27 on effector and memory T cell development become more understood, there may be opportunities select regimens to support central, effector or tissue resident memory cells.…”
Section: Therapeutic Implementation Of Targeting Cd27mentioning
confidence: 99%
“…These results stand in reasonably sharp contrast to the role of these receptors in a vaccine setting, where the blockade of CD27 produces dramatic (>10 fold) inhibition of the primary expansion of CD8 T cells [915, 45, 5759]. Curiously, OX40 can serve as a reasonable substitute to support CD8+ T cell expansion to vaccination, but only in the developmental absence (KO animals) of CD27[12].…”
Section: T Cell Vs B Cell Fauna… All About the Numbersmentioning
confidence: 99%
“…OX40 has a less obscure role in CD4 cell response to vaccination where both CD27 and OX40 signaling are required for peak responses in the WT host [45]. While we have studied this extensively in response to the combined innate/CD40 vaccine adjuvant, others, using a diversity of immunization platforms (adjuvants, in vitro derived DCs, etc) have observed a similar importance for CD27 in a vaccine-elicited T cell response [915, 45, 5759]. In the majority of these systems, this CD27 dependency influences expansion, survival and programming of effectors and memory.…”
Section: T Cell Vs B Cell Fauna… All About the Numbersmentioning
confidence: 99%
See 1 more Smart Citation
“…CLL cells express both cell surface and soluble CD27 [20] and blocking the release of sCD27 using MMP-9 inhibitors induce higher levels of accessory molecules such as CD54, CD80 and CD95 [21]. Recent studies have confirmed functions for CD27 in T cell activation [22,23] and chronic myelogenous leukemia [24]; however, less data is available regarding CD27 function in normal B cells or CLL cells. One study using mouse models suggested a B cell intrinsic function of CD27 in germinal center responses [25].…”
Section: Introductionmentioning
confidence: 99%